Computer Modeling of Physical Processes and Specifics of Relevant Educational Activities - Holovin, Mykola; Holovina, Nina; Holovina, Nelia (Psychological Prospects Journal, 2018)
The article discusses the unique and original psychological model of mental cognitive processes that serve as a foundation for the educational programming. The understanding of the program that is formed in the process of educational action is presented in the form of hierarchical structure. This structure develops through the small, logically finished fragments. Model mechanism of formation of this structure in the process of education is depicted through laconic scheme of three cyclical processes. Mental mechanism of these cycles is explained through the terms of formal logics. The presented model of knowledge formation is universal. It can be used as a platform for development of educational methodology in any sphere of science. The educational programming was chosen for illustration of the model, as this field of science has elaborated hierarchical structure and elements of this structure are the elements of algorithm that can be fast checked for efficiency. The interrelatedness of these schemes is reflected particularly well while modeling the physical processes that have visual component of own development on the screen. All the examples of programming of simple physical processes are discussed within this work.